PENGETAHUAN, SIKAP, DAN PERILAKU SEKSUAL PRANIKAH REMAJA - Muslihatun, Wafi Nur; Kurniati, Ana (Jurnal Kesehatan Ibu dan Anak, 2014)
Premarital sexual behavior is sexual activity involving two people who like each other or love each other before marriage and did before marriage majority of teens having sex the first time while in high school and at the age of about 15-18 years. This study aims to determine the relationship between knowledge and attitude of adolescents with premarital sexual behavior in SMK N 1 Pandak Bantul, Yogyakarta. This study is a cross sectional analytic design, using a sample of 100 students with a simple random sampling on first grade students. Data were collected using a questionnaire on knowledge, attitudes and behavior of adolescent premarital sexual relations. The analysis showed the majority of teens (56%) had high knowledge about premarital sexual behavior, the majority of teens (53%) had a negative attitude toward premarital sexual behavior. As many as 3% of adolescents had sexual intercourse before marriage. There is no significant relationship between knowledge and premarital sexual behavior (p = 0.915), but there is significant association between premarital sexual attitudes and behavior, as well as a protective factor attitudes toward premarital sexual behavior (OR = 0.276 atau 10/2,7; 95% CI = 0.11 -0.69). It is advisable to cultivate and maintain a positive attitude toward adolescent premarital sexual behavior.